2010
DOI: 10.1186/1471-2407-10-354
|View full text |Cite
|
Sign up to set email alerts
|

miR-183 inhibits TGF-β1-induced apoptosis by downregulation of PDCD4 expression in human hepatocellular carcinoma cells

Abstract: BackgroundIn recent years, some miRNAs have been reported to be connected closely with the development of human hepatocellular carcinoma. In our previous studies, a set of miRNAs were revealed to be dysregulated in HCC tissues. However, the functions of these miRNAs in HCC remain largely undefined.MethodsThe expression profiles of miR-183 were compared between HCC tissues and adjacent normal liver tissues using qRT-PCR method. This method was used to screen the potential target genes of miR-183. A luciferase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 30 publications
3
100
2
Order By: Relevance
“…These miRNAs have been found to be overexpressed in colorectal cancer (31) and melanoma (32), showing its oncogenic potential in a variety of neoplastic subtypes. Recently Li and colleagues (18) have shown that miR-183 inhibits apoptosis in human hepatocellular cells by repressing the expression of the proapoptotic gene (PDCD4). This miRNA may thus play an important role in the development of hepatocellular carcinoma in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These miRNAs have been found to be overexpressed in colorectal cancer (31) and melanoma (32), showing its oncogenic potential in a variety of neoplastic subtypes. Recently Li and colleagues (18) have shown that miR-183 inhibits apoptosis in human hepatocellular cells by repressing the expression of the proapoptotic gene (PDCD4). This miRNA may thus play an important role in the development of hepatocellular carcinoma in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Differentially expressed miRNAs of proven significance in the literature were selected for validation anaylsis (18)(19)(20)(21)(22). Selected miRNAs were validated in a combined cohort comprising of the original discovery cohort (n ¼ 19) and an external cohort (n ¼ 26) using TaqMan miRNA assays (hsamiR-9*, Assay ID#:002231; hsa-miR-9, Assay ID#: 00583; hsa-miR-183, Assay ID#:002269; hsa-miR-375, Assay ID#:000564; RNU-48, Assay ID#:001006) on the ABI 7900 HT Fast System (Applied Biosystems) following the manufacturer's instructions.…”
Section: Qpcrmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNA-182 could promote metastasis [97]. MicroRNA-183 inhibits apoptosis [98]. MicroRNA expression can be subjected to regulation with IL-6 [25].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Stem-loop RT-qPCR was performed for miR-21 expression detection as described previously (24), U6 small RNAs were used as an internal control (25). RT-qPCR was carried out using the SuperScript ® III Platinum ® SYBR ® Green One-Step RT-qPCR kit (Thermo Fisher Scientific) according to the manufacturer's instructions.…”
Section: Real-time Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%